A Thermodynamic Study of Methane Hydrates Formation In Glass Beads - Tintin Mutiara; Budhijanto Budhijanto; I Made Bendiyasa; Imam Prasetyo (Department of Chemical Engineering, Universitas Gadjah Mada, 2016)
Natural gas hydrates are non-stoichiometry compounds, in which the molecules of gas are trapped in crystalline cells consisting of water molecules retained by energy of hydrogen bonds. The experiments of Methane hydrate formation are performed at constant temperature in a reactor filled with various sizes of glass beads and water. Methane gas was fed into the reactor at various initial pressures. Equilibrium condition was reached when the system pressure did not change. The experimental results showed that the size of the glass beads gave very small effect on the equilibrium pressure of methane hydrate formation, so the effect could be neglected. In this study, the equation of Langmuir constant was Ci,CH4=(1/RT)exp[A+(B/T)] with the values of A and B for small cages were 6.8465 and 18.0342. The values of A and B for large cages were 7.7598 and 18.0361